Biodegradation and composting of sawdust lignocelluloses waste for use and application as potting at nurseries - Jan Renee Stephanie, Jiorry. (Universiti Malaysia Sarawak (UNIMAS), 2010)
Sawdust is small or fine particles of wood residues resulting from the cutting of the wood. In its raw state, sawdust is harmful to plant because of the tendency of sawdust to absorb nitrogen from the plant causing nitrogen deficiency which subsequently cause dead to the plant. Additionally, the large amount of sawdust disposal has arise the need to be properly disposed. In this study, biodegradation and composting of sawdust were done to be used as potting at nurseries. Optimizations were done to obtain the optimum condition for Cerrena unieolor growth before the actual composting was done. High glucose concentration was observed at day 10 in sterile condition and at day 16 in non sterile condition indicating the activity of the fungi. pH value of 6.0 is found to be efficient for the growth of the fungi. Addition of Cerrena unieolor to the compost had been found effective in degrading lignin content present in the sawdust. The lignin content of the sawdust sample has been decreased from 17.34% to 16.61 % throughout the composting process. Meanwhile, the seed germination test (phytotoxicity test) of the water-extract from sawdust sample inoculated with the fungus showed high germination index (GI) indicating that the extract is non inhibitory to the Kangkong seed. The time of sawdust composting should be longer since sawdust has high CIN ratio.